O trabalho do psicólogo em um Campus do Instituto Federal do Espírito Santo: possibilidades e desafios de uma prática - Nardi, Milena Bertollo (2014)
In this doctoral thesis, I analyze the process of my insertion as a psychologist on a campus of the Federal Institute of Espírito Santo (IFES). This campus had never had before a psychologist in its staff. The overall purpose is to report and analyze the process of planning, setting up and performing interventions, from entering the field, through the search of a theoretical framework and proximity to the students, to the proposition and analysis of the interventions performed. Regarding the methodological aspects, this research was inspired by both: (i) the participatory methodologies of social sciences (participant research, intervention research, and action-research), and clinical research methodology. The participants in the study are: a psychologist in one of the IFES campi (which is also the researcher in this thesis), and students in secondary education technical courses given on such campus. The students are aged between 15 and 19 years. Concerning to the methods of data collection, it is used participant observation, field diaries, questionnaires and focal groups with the students and records of interventions. The data analysis takes place in the following sequence: (i) organization of the information collected; (ii) fluctuating and repeatedly reading the information; (iii) cutting and selection of the most relevant elements according to the research objectives; and (iv) wording of the text. From the theoretical point of view, the articulation between two theories establishes the theoretical foundation based on which this work is conducted: the theory of social representations, as in the discussions proposed by Jovchelovitch, and the theory of human maturation by D.W. Winnicott. The argument put forward is that there is a possible interface between these theories. This interface presents in the professional practice of the psychologist. The performed interventions are based on the belief that the school promotes the development of students and the work of the psychologist. As such, the school is not a diagnostician of problems or an evaluator of the student's intelligence, but a partner in promoting the care and development of students, which lives in society and are part of a cultural heritage and a shared history. The group meetings provides intersubjective exchanges, from which the experiences of each person mingled to form a shared reality. As the main aspects of this research work, I highlight: possible interventions based on the care of every student (without losing the social and the collective aspects as guidance); revitalization of the school space to better provide care and support to adolescents; expansion of the notion of setting and framing other situations in which it is possible to provide support and continence to experiences; importance of analyzing the historical and social context of the individuals in order to prevent stigmatizing and psychological interventions.